Evidence that a Fat-Rich, Thrombogenic Diet Enhances Facfor X Activating Activity of Rat Platelets. - Tremoli, E.; Colucci, M.; Donati, M.B.; Semeraro, N. (Thrombosis and Haemostasis, 1979)
The mechanism by which certain fat-rich diets are able to induce a marked thrombotic tendency in rats is uncertain. Several abnormalities of platelet function have been reported including increased platelet adhesiveness, enhanced platelet aggregability and increased platelet factor 3 activity. We have studied a recently described platelet coagulant activity (factor X activating activity) in rats fed a fat-rich, thrombogenic diet for 1, 2 and 7 weeks as compared to rats fed normal laboratory chow. Whatever the duration of the special feeding period, a highly significant shortening of the special clotting time, devised for measuring this activity, was observed. When platelet coagulant activity of individual “fat-fed“ rats was quantitated by reference to that of the respective randomly paired control animal, a 2-5 fold increase was found as early as after one week of dietary treatment. Partial thromboplastin time, thrombin time and soluble fibrin monomer complexes did not differ in control and treated animals. It seems that platelet coagulant activity, as measured in our test system, is one of the first laboratory parameters to be modified by fat-rich diets. These findings may be relevant to an understanding of the role of platelet coagulant activities other than platelet factor 3 in thrombotic phenomena. Supported by CNR (Italy).